AQUATIC FUNGI OCCURRING IN BRAZIL: A SYSTEMATIC REVIEW - Clarice Maia Carvalho; Pereira, Veluma (South American Journal of Basic Education, Technical and Technological, 2021)
The description of aquatic fungi is still new in the literature, and in Brazil, even with different climatic and hydrological regimes, it still presents a low description of this group of microorganisms. Thus, the objective of this work was to make a systematic review of the aquatic fungi identified in Brazilian biomes. The Scientific Electronic Library Online (SCIELO), Science Direct and Google Scholar databases were used, using the descriptors: Aquatic Fungi Brazil, Fungi igarapé Brazil, Zoosporic fungi Brazil. Studies in the Portuguese and English languages, published from 1999 to May 2019 entered the study. 41 works were selected, described 1293 aquatic fungi, distributed in 328 genera. The Atlantic Forest biome had the highest number of described fungi (49,8%) the samples most used in studies in Brazil were the union of leaves and soil (16%) and the genus Penicillium showed the highest frequency of occurrence in Brazil (3.4%). Thus, this study shows the lack of studies on this group of fungi, mainly in the Pantanal and Pampa biome, where no work has been found, and the need for further studies on the distribution, ecology and identification of aquatic fungi in Brazil.